Ten Years of Reforms: the Impacts of an Increase in the Price of Oil on Welfare - Latif Adam; Esta Lestari (Journal of Indonesian Social Sciences and Humanities, 2008)
The Asian economic crisis that erupted in Indonesia in mid-1997 has resulted in fundamental changes in the structure of the Indonesian economy. For instance, although it was a controversial decision, the fuel subsidy has been extensively reduced since 2000 because of government budget constraints. This paper examines the decision of the government to eliminate the fuel subsidy (and increase the price of fuel) from 2000. It also measures to what extent such a decision has affected the level of peoples welfare in 2005. Using regression analysis, the paper indicates that the decision of the government to increase the price of oil, together with several other variables, correlates negatively with the level of peoples welfare. Based on these findings, it is recommended that the government should be careful in responding to the current conditions in the oil market where the world oil price fluctuates and has increased sharply. Instead of increasing the domestic fuel price, there are several actions that the government can take to respond to the increasing world oil price. Among them are implementing a cross-subsidy policy to redistribute income from higher to lower income groups, making comprehensive plans to increase and achieve lifting oil target, and intensifying efforts to diversify sources of energy.